2022
DOI: 10.3126/jnphyssoc.v8i3.50747
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Magnetic Properties of K2Mn3S4

Abstract: Many opto-electronic and energy efficient devices depend on semiconductors’ direct as well as indirect band gap. Using spin-polarized density functional theory approach, we calculate the electronic structure and magnetic properties of K2Mn3S4. We found that this system has a ferrimagnetic ground state with a saturated magnetic moment of 10μB per unit cell. This was mostly caused by the antiferromagnetic interaction between the Mn (I) and Mn (II) atoms, with individual magnetic moment of 4.2 μB and 4.1 μB, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In one notable study, Li et al [27] recently reported the observation of superconductivity in kagome Rb 2 Pd 3 Se 4 by pressure-induced Lifshitz transition. Recently, by means of DFT calculations, Rb 2 Mn 3 S 4 and K 2 Mn 3 S 4 found magnetic semiconducting materials [28,29]. This finding suggests that the A 2 M 3 X 4 family has potential for exploring superconducting properties, but further investigations are needed to deepen our understanding in this family.…”
Section: Introductionmentioning
confidence: 99%
“…In one notable study, Li et al [27] recently reported the observation of superconductivity in kagome Rb 2 Pd 3 Se 4 by pressure-induced Lifshitz transition. Recently, by means of DFT calculations, Rb 2 Mn 3 S 4 and K 2 Mn 3 S 4 found magnetic semiconducting materials [28,29]. This finding suggests that the A 2 M 3 X 4 family has potential for exploring superconducting properties, but further investigations are needed to deepen our understanding in this family.…”
Section: Introductionmentioning
confidence: 99%